Ruptured giant omphalocele with congenital short small intestine: a case report - Zhang, Wenjing; Wu, Yang; Pan, Cheng; Zhang, Xiangyun; Yan, Hong; Zhang, Li (Frontiers in Nutrition, 2024)
We herein present a case of a ruptured giant omphalocele with congenital short small intestine. Vacuum-sealing drainage and carboxymethylcellulose silver dressing promoted wound healing after repair, avoided abdominal compartment syndrome, and reduced the risks of multiple procedures. We review the perioperative management of omphaloceles in congenital short small intestines.